Nebulous Populism and the Constellation of Agencies within the Philippine Catholic Church - Edryan Paul J. Colmenares (Journal of Moral Theology)
Many scholars who have studied populism consider it a nebulous concept, given the variety of causes that explain its formation. Some view it as emerging from failed liberal democracies with worsening economic inequalities. Others have viewed political disenfranchisement as a leading factor, while a handful relate it to socio-cultural and psychological yearnings for the kind of leader the populist leader embodies. This article explores how the emergence of Duterte’s brand of populism in the Philippines may be understood, considering its history of attempting to establish a liberal democracy. Given that the Philippines is a predominantly Catholic nation, the author also locates the Catholic Church, its hierarchy, and members as a conglomerate of various agents within the populist movement. Lastly, the author explores how populism in the Philippines challenges the church’s desire to be a church for and of the poor.